PENGARUH SISTEM ADMINISTRASI MANUNGGAL SATU ATAP (SAMSAT) TERHADAP KESADARAN MASYARAKAT MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KOTA MANADO - Monding, Juri; Rumapea, Patar; Rorong, Arie (Sam Ratulangi University, 2015)
Abstract : Based from the initial observation that the exictance of Administrative System Manunggal OneRoof (SAMSAT) in Manado city wasn't optimal yet, indicated that there are many people still wouldn't paytaxes on motor vehicles. Thus, this study aims to determine the effect of samsat to people awareness of payingmotor vehicle tax in Manado cityThis study was explorative, with a quantitative approach. Data collected through a questionnairedistributed from 40 community respondents of Manado city that has a motor vehicle but does not pay thevehicle tax. The data collected then analyzed using linear regression analysis and simple correlation analysis.The results showed that SAMSAT aren't still work optimal, as the result samsat disable to encouragethe public to pay vehicle taxes.SAMSAT was effected the public awareness to pay motor vehicle tax in Manado city. Suggested, inorder Samsat can improve the quality of service so as to encourage people to pay vehicle taxes.Keywords: SAMSAT, public awareness paying motor vehicle tax